A Moderating Role Of Good Governance in the Relationship Between Carbon Emission Disclosure, Green Innovation, Eco-Efficiency, ESG, and Firm Value in Energy Sector - Fitri Nurhayati; Rofiqah Wahdah; Yanuar Bachtiar; Muhammad Maladi; Dini Rusqianti (Politeknik Ganesha Medan, 2026)
This study examines the effect of carbon emission disclosure, green innovation, eco-efficiency, and environmental, social, and governance (ESG) on firm value, with good corporate governance as a moderating variable, in energy sector companies listed on the Indonesia Stock Exchange during the 2021–2024 period. A quantitative approach was employed using secondary data derived from annual and sustainability reports. The sample was selected through purposive sampling, resulting in 108 firm-year observations after outlier removal. Data were analyzed using panel data regression and Moderated Regression Analysis (MRA), preceded by model selection and classical assumption tests. Firm value was measured using Tobin’s Q, while carbon emission disclosure, green innovation, eco-efficiency, and ESG were proxied using respective sustainability indicators. Good corporate governance was measured by institutional ownership. The partial test results indicate that carbon emission disclosure has a positive and significant effect on firm value (p < 0.01). In contrast, green innovation has a negative and significant effect (p < 0.01), and ESG also shows a negative and significant effect (p < 0.05), while eco-efficiency does not have a significant effect (p > 0.05). The model explains 7.6% of the variation in firm value (R² = 0.076). These findings suggest that sustainability practices do not uniformly enhance firm value, particularly in the short term, and highlight the importance of governance quality in strengthening sustainability strategies in emerging markets..